2016
DOI: 10.1017/s0305000916000222
|View full text |Cite
|
Sign up to set email alerts
|

Age and input effects in the acquisition of mood in Heritage Portuguese

Abstract: The present study analyzes the effect of age and amount of input in the acquisition of European Portuguese as a heritage language. An elicited production task centred on mood choice in complement clauses was applied to a group of fifty bilingual children (six- to sixteen-year-olds) who are acquiring Portuguese as a minority language in a German dominant environment. The results show a significant effect of the age at testing and the amount of input in the acquisition of the subjunctive. In general, acquisition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
50
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 53 publications
8
50
1
7
Order By: Relevance
“…This means that the accumulated amount of contact with the HL modulates the development of the HL system in the domain of direct object expression. Similar effects of amount of input on the grammatical development of home languages have been found in many other domains (Flores et al 2017b for mood choice in EP; Gathercole and Thomas 2009 for grammatical gender in Welsh; Thordardottir 2015, for English and French verbal morphology).…”
Section: Discussionsupporting
confidence: 62%
“…This means that the accumulated amount of contact with the HL modulates the development of the HL system in the domain of direct object expression. Similar effects of amount of input on the grammatical development of home languages have been found in many other domains (Flores et al 2017b for mood choice in EP; Gathercole and Thomas 2009 for grammatical gender in Welsh; Thordardottir 2015, for English and French verbal morphology).…”
Section: Discussionsupporting
confidence: 62%
“…Participants were selected based on their age at onset of bilingualism, which was taken as their age of arrival in the United Kingdom. As Flores, Santos, Jesus, and Marques () have pointed out, adult heritage speaker investigations “cannot distinguish effects of acquisition from effects of subsequent language attrition” (p. 797). This is especially the case for late‐acquired properties, like noun and relative clauses, which have been reported not to stabilize before the ages of 5 or 6 years in monolingual Turkish speakers (Aksu‐Koç, ; Slobin, ).…”
Section: Methodsmentioning
confidence: 99%
“…). Similarly, whereas chronological age has been shown to lead to improvement of HL performance (e.g.,Armon-Lotem, Walters, & Gagarina, 2011;Flores, 2015;Flores, Santos, Jesus, & Marques, 2017), other studies have found no or…”
mentioning
confidence: 90%